Introduction - Jana S. Rošker (Asian Studies, 2021)
The present special issue deals with the period which embraces eight decades that were crucial to the development and establishment of present-day China. The period under research spans from the threshold of the previous century up until the 1980s, i.e. until the margins of the new millennium.